THE CATEGORY OF SPACE AND TIME OF TRIPLITS (Scientific journal of the Fergana State University, 2023)
The article deals witle the relationship betweea art spas and time based of rhythmic-intonational units in the teinity. positive effect on the content and form of the poem by uens of the treinity triangie reveealed winli axauvle of triplits of Anwar Abidjon.